(untitled) (Global Journal of Management and Business Research, 2024)
I Introduction There is a vast amount of studies and literature on the concepts of Value Chain and Competitive Strategy which were originally proposed by Michael Porter 1 Since then these two concepts have supported the development of organizations in their quest to enhance their competitiveness in the markets The concept of value in products has gained significant importance in ensuring their success Today discussing value in products or services is a term related to customer perception It is a term that is subject to how the customer perceives the attributes of the product or service In other words value has a significant subjective component as it depends on multiple factors for evaluation by the end consumer Nevertheless organizations are obligated to continue creating value in their processes that integrate the Value Chain to remain competitive in the market